Game Production Studies 2021
DOI: 10.5117/9789463725439_intro
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Why Game Production Matters?

Abstract: In the introduction, the editors of this collection argue for the importance of game production studies at a point when the public awareness about the production context of video games has, arguably, never been higher. With so many accounts of video game development permeating player and developer communities, the task of game production studies is to uncover the economic, cultural, and political structures that influence the final form of games by applying rigorous research metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…They do so through conducting ethnographies and interviews of game developers and their studios (e.g., ; carrying out political-economic analyses of game production, distribution, and corporate documentation ; and more broadly studying "the social and historical forces that inform the design […] and the perceptions of those who create" them to understand the choices developers make (de Smale et al, 2019, p. 392). These choices and their context vary greatly within their global, local and/or hobbyist contexts, furthermore depending on platform, funding and business models (Sotamaa & Švelch, 2021;cf. Garda & Grabarczyk, 2016;Švelch, 2021;Šisler, et al, 2022).…”
Section: Producing and Playing With Religionmentioning
confidence: 99%
“…They do so through conducting ethnographies and interviews of game developers and their studios (e.g., ; carrying out political-economic analyses of game production, distribution, and corporate documentation ; and more broadly studying "the social and historical forces that inform the design […] and the perceptions of those who create" them to understand the choices developers make (de Smale et al, 2019, p. 392). These choices and their context vary greatly within their global, local and/or hobbyist contexts, furthermore depending on platform, funding and business models (Sotamaa & Švelch, 2021;cf. Garda & Grabarczyk, 2016;Švelch, 2021;Šisler, et al, 2022).…”
Section: Producing and Playing With Religionmentioning
confidence: 99%
“…They do so through conducting ethnographies and interviews of game developers and their studios (e.g., O'Donnell, 2014;Kerr, 2017); carrying out political-economic analyses of game production, distribution, and corporate documentation (Kerr, 2006;Nieborg, 2011Nieborg, , 2021; and more broadly studying "the social and historical forces that inform the design […] and the perceptions of those who create" them to understand the choices developers make (de Smale et al, 2019, p. 392). These choices and their context vary greatly within their global, local and/or hobbyist contexts, furthermore depending on platform, funding and business models (Sotamaa & Švelch, 2021;cf. Garda & Grabarczyk, 2016;Keogh, 2021Keogh, , 2022Švelch, 2021;Šisler, et al, 2022).…”
Section: Producing and Playing With Religionmentioning
confidence: 99%
“…The complex interdisciplinary process in game development, the demand for specialized tools and systems, and the need to maintain creativity show the need for researching game development in the wild (Engström, 2020). The game studies community also shows an increased interest to pursue this line of research (Sotamaa & Svelch, 2021). Currently, most studies can be found in the management and software engineering community.…”
Section: Game Developmentmentioning
confidence: 99%